2016
DOI: 10.1007/s10995-016-1939-7
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Birth Weight for Gestational Age in Relation to Risk of Hospitalization with Primary Hypertension in Children and Young Adults

Abstract: Introduction Low birth weight has been associated with an increased risk of hypertension in children. Less clear is whether high birth weight is also associated with risk. We evaluated overall and age-specific risks of primary hypertension in children and young adults associated with birth weight and birth weight for gestational age. Methods We conducted a population-based case-control study using linked Washington State birth certificate and hospital discharge data from 1987–2003. Cases were persons hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
(47 reference statements)
1
21
0
1
Order By: Relevance
“…Early life factors, dietary behavior, physical activity, and other factors play an important role on influencing HBP mechanisms in youth. We found that using two different HBP definitions, preterm delivery, cesarean delivery, and family hypertension history were risk factors for HBP in children, which was consistent with previous studies [33,34]. In the previous review, the relationship between high birth weight and HBP in children and adolescents was inconsistent, with studies reporting positive, inverse, or no associations [35].…”
Section: Discussionsupporting
confidence: 88%
“…Early life factors, dietary behavior, physical activity, and other factors play an important role on influencing HBP mechanisms in youth. We found that using two different HBP definitions, preterm delivery, cesarean delivery, and family hypertension history were risk factors for HBP in children, which was consistent with previous studies [33,34]. In the previous review, the relationship between high birth weight and HBP in children and adolescents was inconsistent, with studies reporting positive, inverse, or no associations [35].…”
Section: Discussionsupporting
confidence: 88%
“…In the population-based study of Chinese children aged 3–6 years, children of higher BW percentiles were found to have a significantly increased risk of hypertension in both boys and girls, comparing to the lowest quartile of the BW percentile [ 14 ]. A population-based case–control study in the USA [ 15 ] found that BW ≥4000 g and being LGA were significantly associated with primary hypertension in adolescents and young adults 15–24 years of age, but not in children 8–14 years of age. However, in contrast to our study, several studies have found no significant associations between HBW and HBP in children in multivariate analyses after adjustment for confounding factors including current childhood BMI [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al reported that HBW (BW ≥4000 g or ≥90th percentile for the gestational age) was related to a higher risk of HBP and hypertension in younger children, but with a lower risk in older adults, compared to those with normal birth weight (BW 2500–4000 g or the 10th–90th percentiles for gestational age) [ 10 ]. Even though epidemiological studies have examined the association between HBW and HBP [ 11 – 13 ] or hypertension [ 14 , 15 ] among children and adolescents, the results have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, a study examining the incidence of neonatal enterocolitis in those born SGA showed a higher percentage of neonatal enterocolitis in those born with a birthweight less than the 2.3rd percentile and between the 2.3rd and 5th percentile when compared to those born between the 5th and 10th percentile, although this was not statistically significant [15]. Other research concerning health consequences of being born SGA, including primary hypertension risk [16], adult hormonal response to psychosocial stress [17], long-term maternal cardiovascular morbidity [18], and risk of long-term maternal renal disease [19] define SGA as below the 10th percentile, preventing stratification of risk based on differing percentiles and possibly including patients who may not, in fact, be at risk.…”
Section: Tablementioning
confidence: 99%